Effectiveness of the PRI (Psycho Religious Intervention) Model to Improve the Physical Well-Being of Cancer Patients - Priyanto Priyanto; Sukarno Sukarno; Gipta Galih Widodo; Salma Widya Oktaviani; Almera Sinta Ramadhani (Indonesian Journal of Global Health Research, 2026)
Cancer imposes a significant health burden, encompassing not only physical symptoms like pain and fatigue but also substantial psychological and spiritual distress, which collectively diminish patients' overall well-being. Given the high cost of care in Indonesia, comprehensive supportive interventions are urgently needed. This study aimed to test the effectiveness of the Psycho Religious Intervention (PRI) model an innovative nursing therapy integrating psychoeducation and contemplative (tafakur) prayer on improving cancer patients' physical well-being. A randomized controlled trial (RCT) design with a pre-post test method was employed. Sixty cancer patients at Dr. Adhyatma Hospital were recruited and equally randomized into intervention and control groups. The intervention group received the PRI model for 30 minutes per session, twice daily, for four consecutive days. Effectiveness analysis using independent-samples t-tests revealed that the PRI model significantly improved physical well-being. The intervention group demonstrated a qualitative improvement from moderate (mean 159.07) to high well-being (mean 181.33), surpassing the control group (mean 161.20). Specifically, the model significantly reduced pain (p=0.010), physical fatigue (p=0.036), and sleep disturbance (p=0.016), although nausea reduction was marginally significant (p=0.058). The PRI Model is established as an effective, evidence-based self-care modality, proving highly relevant for holistic palliative care.